Dermatologic adverse events associated with afatinib: an oral ErbB family blocker. Issue 6 (June 2013) - Lacouture, Mario E; Schadendorf, Dirk; Chu, Chia-Yu; Uttenreuther-Fischer, Martina; Stammberger, Uz; O'Brien, Dennis; Hauschild, Axel
Dermatologic adverse events (AEs) are frequently observed in patients receiving EGF receptor (EGFR; also known as ErbB1) tyrosine kinase inhibitor therapy. The impact of these AEs goes beyond cosmesis to the discomfort from itching, pain and secondary infections, all of which may significantly impact on patient well-being, adherence and clinical outcomes. Afatinib is a potent, irreversible, oral, ErbB family blocker, inhibiting EGFR (ErbB1), HER2 (ErbB2) and ErbB4 receptor kinases. It also inhibits transphosphorylation of ErbB3. Similar to EGFR inhibitors, dermatologic AEs have been frequently observed in patients treated with afatinib. Papulopustular (acneiform) rash, pruritus, xerosis, paronychia and alopecia will require patient education and proactive treatment interventions. This article summarizes current data on the dermatologic AEs associated with afatinib treatment across the clinical trial program, and provides strategies for their effective management.